The Influence of Medicine Ball Throw and Resistance Bands on Throwing Ability in Football Games of SSB Joma Putra Sunda Students - Sukmadini, Irwan; Wardiah, Dessy; Imansyah, Farizal (Yayasan Sembilan Pemuda Indonesia, 2023)
This research is an experiment with the pretest-posttest control group design method. The type of research used in this study is a type of experimental research with a quasi-experimental design. This research is experimental research and the research design used is Quasi Experimental Design, namely the Group Pretest Posttest Design. The sample used in this study were SSB Joma Putra Sunda Palembang players aged 10-16 years in 2023, totaling 15 players. The sampling technique in this study used a systematic sampling technique and an ordinal pair system. This research as a whole used test, measurement and documentation methods. The results of the study mean/average results of throws in SSB Joma Putra Sunda Palembang players in the medicine ball practice group after being treated experienced an increase from the pre-test of 7.62 to the post-test of 8.65 or with an increase percentage of 12.90%, for the mean/average results of throws in the SSB Joma Putra Sunda Palembang Resistance band training group from the pre-test of 7.49 to the post-test of 8.64 or with a percentage increase of 14.48%. while for the mean/average result of throwing in the SSB Joma Putra Sunda Palembang group from the pre-test of 9.60 to the post-test of 10.75 or with an increase percentage of 9.71%. So that it can be concluded that there is a significant influence between medicine ball throw and resistance bands on the ability to throw into football games in SSB Joma Putra Sunda Palembang students.